Effects of Methionine-Cysteine Amino Acid Supplementations in the Aflatoxin B1 Contaminated Diet on Broiler Production Performance - Listya Purnamasari; Ali Agus; Cuk Tri Noviandi (Buletin Peternakan, 2019)
This research aimed to observe the interaction of methionine-cysteine amino acid supplementation to decrease the effect of aflatoxin B1 (AFB1) on diet against production performance of broiler chicken. A number of 240 mixed sex broiler chickens were treated in 9 treatments by factorial design 3 x 3 with methionine-cysteine amino acid (M+C) (75,100, dan 125%) factors and AFB1 levels (0, 200, dan 400 ppb). Variables observed were: Weight gain, feed consumption, and feed conversion ratio (FCR). The results showed that increased AFB1 content in diet from 0 to 400 ppb increased chicken body weight (P <0.05) in each age group. The high body weight was balanced with high feed consumption along with increased nutrient needs, mainly sulfuric amino acid (M+C) as the precursor of glutathione to eliminate toxic through conjugation reactions. The interaction effect was firstly occurred between M + C and AFB1 treatment (P <0.05). Meanwhile increased supplementation of M + C from 75 to 125% caused decreased feed consumption in each age group of chickens, but increased AFB1 levels further increased feed consumption (P<0.05). The interaction effect between the level of M + C and AFB1 contamination in diets on feed consumption were seen in 21-day-old chickens (P<0.05). FCR was also increased (P <0.05) with the reduction of M + C content in diet at 7 days old. The effect of AFB1 on diet and interaction between M + C and AFB1 on chicken FCR in this study was not significant in all age groups. It can be concluded from the current study that supplying methionine-cystine amino acid with 75, 100 and 125% in AFB1 contaminated diet of 0, 200 and 400 ppb improves the performance of broiler chicken production.